A functional assay for the clinical annotation of genetic variants of uncertain significance in Diamond–Blackfan anemia. Issue 8 (28th May 2018) - Aspesi, Anna; Betti, Marta; Sculco, Marika; Actis, Chiara; Olgasi, Cristina; Wlodarski, Marcin W.; Vlachos, Adrianna; Lipton, Jeffrey M.; Ramenghi, Ugo; Santoro, Claudio; Follenzi, Antonia; Ellis, Steven R.; et al.
Abstract: Diamond–Blackfan anemia (DBA) is a rare genetic hypoplasia of erythroid progenitors characterized by mild to severe anemia and associated with congenital malformations. Clinical manifestations in DBA patients are quite variable and genetic testing has become a critical factor in establishing a diagnosis of DBA. The majority of DBA cases are due to heterozygous loss‐of‐function mutations in ribosomal protein (RP) genes. Causative mutations are fairly straightforward to identify in the case of large deletions and frameshift and nonsense mutations found early in a protein coding sequence, but diagnosis becomes more challenging in the case of missense mutations and small in‐frame indels. Our group recently characterized the phenotype of lymphoblastoid cell lines established from DBA patients with pathogenic lesions in RPS19 and observed that defective pre‐rRNA processing, a hallmark of the disease, was rescued by lentiviral vectors expressing wild‐type RPS19. Here, we use this complementation assay to determine whether RPS19 variants of unknown significance are capable of rescuing pre‐rRNA processing defects in these lymphoblastoid cells as a means of assessing the effects of these sequence changes on the function of the RPS19 protein. This approach will be useful in differentiating pathogenic mutations from benign polymorphisms in identifying causative genes in DBA patients. Abstract : Heterozygous loss‐of‐function mutations in RPS19 cause Diamond‐Blackfan anemia (DBA). Lymphoblastoid cell lines with pathogenic lesions in RPS19 show defective pre‐rRNA processing that is rescued by lentiviral vectors expressing wild‐type RPS19. We exploited this complementation assay to differentiate pathogenic mutations from benign variants that have no effect on protein function, thus clarifying their clinical relevance.